Cystic Echinococcosis of Camels: 12S rRNA Gene Variation Revealed Changing Pattern of Genetic Diversity Within Echinococcus granulosus sensu lato in the Middle East and North/Sub-Saharan Africa - Dehghani, Mansoureh; Mohammadi, Mohammad Ali; Hemmati, Sahel; Nasibi, Saeid; Rostami, Sima; Fasihi Harandi, Majid (Frontiers in Veterinary Science, 2020)
Cystic echinococcosis (CE) is one of the most widespread zoonotic diseases, with considerable public health and economic importance. Camels play a significant role in transmission cycle of E. granulosus especially, in the Middle East and North Africa (MENA). The present study aimed to identify the genetic variation and haplotype distribution of camel isolates of E. granulosus sensu lato using all existing E. granulosus mitochondrial DNA data from camels in different parts of the world. Sequence data from 1144 camel isolates of E. granulosus s.l. available in the NCBI GenBank including 57 camel hydatid cysts collected in central Iran were used to analyze the nature of genetic variation within the camel isolates of E. granulosus s.l. in MENA region. Fifty-seven camel isolates were also PCR-sequenced on mitochondrial 12S rRNA gene. Haplotype network analysis revealed seven different haplotypes clustered into four major groups. E. intermedius G6 was identified as the most commonly represented genotype in camels followed by G1. Mitochondrial 12S rRNA gene sequence analysis on 57 camel isolates identified three different genotypes, including E. intermedius / G6 (35/57, 61.4%), E. granulosus sensu stricto / G1-G3 (21/57, 36.8%) as well as one isolate identified as E. ortleppi / G5 (1/57, 1.8%). The number of base substitutions per site over 420 positions of partial 12S rRNA gene sequences were shown as 0.000 and 0.004 for E. intermedius (G6) corresponding to the Middle East and sub-Saharan isolates respectively. Camel isolates of E. granulosus in the Middle East demonstrated greater genetic heterogeneity than North / sub-Saharan isolates with significant intraspecific variation among three species and six different haplotypes. E. intermedius (G6 genotype) was shown to be the most common species in the world camel population. In conclusion, camels showed to be an important intermediate host species in the MENA region with different patterns of genetic variation between the Middle East and Africa.